Aluminum-plastic film coating, aluminum-plastic film and application of aluminum-plastic film

By using porous active adsorption materials with high specific surface area and Mohs hardness on aluminum-plastic films, combined with modifiers and binders, a coating is formed to adsorb the internal gas of the battery and improve impact resistance, the battery leakage and edges are solved. The problem of damage has significantly improved the overall performance and stability of the battery.

CN119286316APending Publication Date: 2025-01-10ZHEJIANG LIWINON ELECTRONIC TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411339647.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing aluminum-plastic films are prone to liquid leakage in soft-pack batteries. The main reason is that the gas production inside the battery cell and the R angle or the edge of the bottom of the pit are damaged, and the lack of effective gas adsorption and impact resistance.

Method used

Porous active adsorbent materials with specific surface area ≥150m2/g and Mohs hardness ≥3 are used as the main components of aluminum-plastic film coatings. Combined with modifiers, binders and coupling agents, a coating is formed to adsorb the internal gas of the battery and improve it. Impact resistance and avoid damage.

Benefits of technology

Effectively adsorb the internal gas of the battery, reduce liquid consumption, improve battery performance, and protect R-angle aluminum foil residue under impact, significantly reducing the risk of liquid leakage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286316A_ABST
    Figure CN119286316A_ABST
Patent Text Reader

Abstract

The invention discloses an aluminum-plastic film coating, an aluminum-plastic film and application of the aluminum-plastic film. The aluminum-plastic film coating comprises an active adsorption material, a modifier, a binder, a coupling agent and an oily solvent, the active adsorption material is a porous material with the specific surface area larger than or equal to 150 m < 2 > / g and the Mohs hardness larger than or equal to 3, and the modifier comprises an isobutylene-maleic anhydride copolymer. The active adsorption material has more surface active sites, a surface micro-nano structure and a large number of micropores, and Coulomb force between the micropores and the active adsorption material generates an adsorption effect; the formed coating is in contact with the electrolyte to achieve the electrolyte retention effect, and the electrolyte is consumed in the later period of circulation, the active adsorption material can effectively adsorb gas generated inside and release part of the electrolyte, so that various properties of the battery are improved. And the active adsorption material is sufficient to enable the coating to endow the aluminum-plastic film with more effective impact resistance, so that a supporting effect can be achieved in the pit punching process of the aluminum-plastic film, and R-angle aluminum foil residues under the high pit punching depth are protected.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to aluminum-plastic film coatings, aluminum-plastic films and applications thereof. Background Art

[0002] Soft-pack batteries generally use aluminum-plastic film as a protective film for the battery cell. The existing aluminum-plastic film structure has polyethylene terephthalate (PET) / nylon layer, aluminum foil layer and cast polypropylene (CPP) layer in sequence, which are formed by multi-layer co-extrusion casting or multi-layer lamination process. The failure of aluminum-plastic film in soft-pack batteries is mainly reflected in the leakage phenomenon. In addition to the reasons for abnormal packaging, one of the reasons for leakage is the generation of gas inside the battery cell, and another reason is the damage of the R corner or the bottom edge of the pit. Therefore, it is necessary to provide an aluminum-plastic film that has the function of absorbing the gas inside the battery and has good impact resistance to avoid damage. Summary of the invention

[0003] The present application aims to solve at least one of the technical problems existing in the prior art. To this end, the present application proposes an aluminum-plastic film coating, an aluminum-plastic film and its application, wherein the coating formed on the aluminum-plastic film can effectively absorb the gas inside the battery and has good impact resistance to avoid damage.

[0004] In a first aspect of the present application, an aluminum-plastic film coating is provided, wherein the aluminum-plastic film coating comprises an active adsorption material, a modifier, a binder, a coupling agent and an oily solvent, wherein the active adsorption material has a specific surface area of ​​≥150m 2 / g and a porous material with a Mohs hardness of ≥3, wherein the modifier comprises an isobutylene-maleic anhydride copolymer.

[0005] The aluminum-plastic film coating according to the first aspect of the present application has the following beneficial effects:

[0006] Active adsorption materials that meet the above characteristics have more surface active sites and surface micro-nano structures, and a large number of micropores below 1nm are formed inside. The Coulomb force between the micropores and the active adsorption materials produces adsorption; the formed coating can achieve the effect of retaining the electrolyte when in contact with the electrolyte, and when the electrolyte is consumed in the later stage of the cycle, the active adsorption material can effectively absorb the gas generated inside and release part of the electrolyte, thereby improving the various performances of the battery. In addition, the active adsorption material that meets the above Mohs hardness conditions is sufficient to enable the coating to give the aluminum-plastic film more effective impact resistance, so that it can play a supporting role in the aluminum-plastic film cratering process and protect the R-corner aluminum foil residue under high cratering depth.

[0007] In addition, it has been noticed in practice that active adsorption materials with high specific surface areas are prone to capillary water absorption. If the active adsorption materials are simply coated, moisture may be brought into the battery cell, generating gas and causing a decrease in battery performance. The modifier isobutylene-maleic anhydride copolymer is an amphiphilic polymer that can be evenly distributed on the surface of the active adsorption material through solvent dissolution. After heat treatment, the CO bond in the CONH4 group is broken and an amide group is generated, thereby avoiding the capillary water absorption of the active adsorption material and further reducing gas generation.

[0008] In some embodiments of the present application, the mass ratio of the modifier to the active adsorption material is 0.00005 to 0.0002:1, for example, it can be 0.00005:1, 0.00006:1, 0.00007:1, 0.00008:1, 0.00009:1, 0.0001:1, 0.00012:1, 0.00014:1, 0.00016:1, 0.00018:1, 0.0002:1.

[0009] In some embodiments of the present application, the mass ratio of the binder to the active adsorption material is 1 to 3:10, for example, 1:10, 2:10, or 3:10.

[0010] In some embodiments of the present application, the mass ratio of the coupling agent to the active adsorption material is 1 to 3:10, for example, 1:10, 2:10, or 3:10.

[0011] In some embodiments of the present application, the active adsorption material includes at least one of γ-alumina, titanium oxide, boehmite, and pseudo-boehmite.

[0012] In some embodiments of the present application, the active adsorption material includes at least one of γ-alumina and pseudo-boehmite.

[0013] In some embodiments of the present application, the active adsorption material includes γ-alumina. The use of γ-alumina not only achieves impact resistance and gas adsorption, but also avoids the introduction of new impurities (such as activated carbon, molecular sieves, titanium hydroxide, titanium oxide, etc.) into the battery cell. In contrast, the Mohs hardness of pseudo-boehmite and boehmite is slightly lower, and the improvement of mechanical properties such as impact resistance of aluminum-plastic film is slightly insufficient.

[0014] In some embodiments of the present application, the purity of γ-alumina is ≥99.9%, and the specific surface area is ≥150m 2 / g.

[0015] In some embodiments of the present application, the purity of pseudo-boehmite is ≥ 99.9%, and the specific surface area is ≥ 230 m 2 / g.

[0016] In some embodiments of the present application, the Mohs hardness of pseudo-boehmite and boehmite is 3-4, the Mohs hardness of γ-alumina is 6-8, and the Mohs hardness of titanium oxide is 5-6.

[0017] In some embodiments of the present application, the binder includes at least one of polyvinylidene fluoride (PVDF), styrene-acrylic acid copolymer, and polyvinyl acetate.

[0018] In some embodiments of the present application, the polyvinylidene fluoride binder is combined with a modifier and an active adsorption material to achieve better effects on improving the impact resistance and temperature resistance.

[0019] In some embodiments of the present application, the coupling agent includes at least one of an aluminate coupling agent, a phthalate coupling agent, a silane coupling agent, a phosphate coupling agent, and a borate coupling agent. The above coupling agent has an inorganic affinity group and an organic affinity group, and adding it to the coating can improve the dispersion of the active adsorption material in the organic solvent.

[0020] In some embodiments of the present application, the coupling agent includes an aluminate coupling agent. The molecular formula of the aluminate is [Al(OR)3] n (R is an alkyl or allyl group), as an aluminum source, no new impurity elements are introduced. In addition, compared with other coupling agents (such as borate coupling agents, phosphate coupling agents, and silane coupling agents), it is light in color, non-toxic, has little odor, and is low in price.

[0021] In some embodiments of the present application, the oily solvent includes a first solvent and a second solvent; wherein the first solvent includes at least one of N-methylpyrrolidone (NMP), dimethylformamide, carbon tetrachloride, toluene dichloroethane, acetone, and isopropanol; and the second solvent includes at least one of dimethyl carbonate and N,N-dimethylformamide. Since the active adsorption material itself has a large specific surface area, it is difficult to wet and disperse it evenly in water, so an oily solvent is used to disperse it. To this end, the first solvent is used to dissolve or disperse the active adsorption material and the coupling agent, and the second solvent is used to dissolve or disperse the modifier, so that several components can achieve a high dispersion and improve the adsorption effect on the gas.

[0022] In some embodiments of the present application, the mass ratio of the first solvent to the active adsorption material is 100:10-15, for example, 100:10, 100:11, 100:12, 100:13, 100:14, or 100:15.

[0023] In some embodiments of the present application, the ratio of the modifier to the second solvent is 1g:0.5~1.5L, for example, it can be 1g:0.5L, 1g:0.6L, 1g:0.7L, 1g:0.8L, 1g:0.9L, 1g:1.0L, 1g:1.1L, 1g:1.2L, 1g:1.3L, 1g:1.4L, 1g:1.5L.

[0024] There are many active sites on the surface of active adsorption materials, and the surface of active adsorption materials has micro-nano structures, forming many channels and mesopores. The Coulomb force between the mesopores and the active adsorption materials produces adsorption, which can adsorb the gas generated inside the battery cell. The use of inorganic ceramic materials such as γ-alumina and polyvinylidene fluoride can make the inner layer of the aluminum-plastic film have high temperature resistance, flame retardancy and impact resistance, which can protect the battery cell when the battery cell fails, and protect the aluminum-plastic film from being easily damaged at the R corner under high pit depth.

[0025] In a second aspect of the present application, an aluminum-plastic film is provided, which includes a first insulating polymer layer, an aluminum foil layer, and a second insulating polymer layer arranged in sequence. A functional coating is also provided on the side of the first insulating polymer layer away from the aluminum foil layer, and the functional coating is made of the aforementioned aluminum-plastic film coating.

[0026] The second insulating polymer layer provides certain heat resistance, wear resistance, puncture resistance and bending resistance, and plays a good protective role on the aluminum foil layer. It is usually made of at least one material such as nylon, polyester (such as polyethylene terephthalate), etc. The first insulating polymer layer provides heat sealing effect and is made of at least one material such as polypropylene, polyethylene, ethylene acrylic acid copolymer, ion cross-linked polymer resin, etc.

[0027] In some embodiments of the present application, the aluminum-plastic film includes a polypropylene layer, an aluminum foil layer and a nylon layer arranged in sequence, and a functional coating is further provided on the side of the polypropylene layer away from the aluminum foil layer, and the functional coating is made of the aforementioned aluminum-plastic film coating.

[0028] In some embodiments of the present application, the aluminum-plastic film includes a dent area, and the functional coating covers the dent area.

[0029] In some embodiments of the present application, the aluminum-plastic film further includes a heat-sealing area around the punching area, and the heat-sealing area includes a top sealing area, a side sealing area and a second sealing area.

[0030] In some embodiments of the present application, the area of ​​the functional coating on the aluminum-plastic film is more than 1.1 times the area of ​​the dent area.

[0031] In some embodiments of the present application, the distance from the edge of the functional coating on the aluminum-plastic film to the inner side of the heat-sealed area is ≥5 mm, wherein the inner side is the side close to the crater area.

[0032] If the area of ​​the functional coating is too large and is close to the inner side of the heat seal, discontinuous heat sealing (dot-shaped) may occur in the heat seal area during the melting process of the heating polypropylene layer. During the long-term electrolyte immersion process, it is easy to penetrate and leak, affecting the heat sealing effect and causing leakage. If the area of ​​the functional coating is too small, it cannot better protect the R-corner aluminum foil residue under the punching pit.

[0033] In some embodiments of the present application, the aluminum-plastic film satisfies T / 1000≤M×D≤A;

[0034] Wherein, T is the depth of the scouring pit and is less than 15 mm;

[0035] M is the Mohs hardness of the active adsorption material;

[0036] D is the thickness of the functional coating, and D is 2 to 10 μm;

[0037] A is the thickness of the aluminum foil layer.

[0038] In order to ensure that the aluminum-plastic film can protect the residual aluminum foil at the R corner under high impact pitting, and does not occupy too much battery cell space, and avoid being too thick to affect the ED of the battery cell itself, the aluminum-plastic film must meet the above conditions.

[0039] The present application also relates to a method for preparing an aluminum-plastic film, comprising the following steps:

[0040] The aluminum-plastic film coating is applied to the crater area and heat treated to form a functional coating.

[0041] In some embodiments of the present application, the temperature of the heat treatment is 80-150°C, for example, it can be 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, or 150°C.

[0042] In some embodiments of the present application, the coating method is gravure intermittent coating.

[0043] In a third aspect of the present application, a lithium-ion battery is provided. The lithium-ion battery comprises the aforementioned aluminum-plastic film.

[0044] In some embodiments of the present application, the lithium-ion battery comprises a battery core and an aluminum-plastic film covering the battery core. The battery core comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, and the positive electrode sheet, the negative electrode sheet and the separator are wound to obtain a battery core and a lithium-ion battery.

[0045] In some embodiments of the present application, the positive electrode current collector and the negative electrode current collector are independently selected from at least one of metal materials including metal foil (such as aluminum foil, silver foil, tin foil, iron foil, titanium foil, nickel foil, copper foil or alloy foil of the above metals), metal mesh (such as aluminum mesh, silver mesh, tin mesh, iron mesh, titanium mesh, nickel mesh, copper mesh or alloy mesh of the above metals).

[0046] In some embodiments of the present application, the positive (negative) electrode sheet includes a positive (negative) electrode current collector and a positive (negative) electrode active material layer.

[0047] In some embodiments of the present application, the positive electrode active material layer includes a positive electrode active material, including but not limited to at least one of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel manganese aluminum oxide, etc. The negative electrode active material layer includes a negative electrode active material, including but not limited to at least one of carbon material, silicon material, carbon silicon material, etc.

[0048] In a fourth aspect of the present application, an electrical device is provided, which includes the aforementioned lithium-ion battery.

[0049] Among them, electrical equipment refers to any equipment that can use electrical energy and convert it into mechanical energy, thermal energy, light energy or other one or more forms of energy, such as electric motors, electric heat engines, electric light sources, etc. Among them, mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. Mobile devices can be mobile phones, laptops, drones, sweeping robots, electronic cigarettes, etc.; electric vehicles can be pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.

[0050] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 It is a schematic structural diagram of an aluminum-plastic film according to an embodiment of the present application.

[0052] Reference numerals: aluminum-plastic film 100 , punching area 110 , side sealing area 120 , top sealing area 130 , second sealing area 140 , air bag area 150 , an upper sealing area 160 , a first functional coating 210 , and a second functional coating 220 . DETAILED DESCRIPTION

[0053] The following will clearly and completely describe the concept of the present application and the technical effects produced in combination with the embodiments, so as to fully understand the purpose, features and effects of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of them. Based on the embodiments of the present application, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present application.

[0054] The embodiments of the present application are described in detail below. The described embodiments are exemplary and are only used to explain the present application, and should not be understood as limiting the present application.

[0055] In the description of this application, "several" means more than one, "many" means more than two, "greater than", "less than", "exceed", etc. are understood to exclude the number itself, "above", "below", "within", etc. are understood to include the number itself, and "about" means within the range of ±20%, 10%, 8%, 5%, 4%, 3%, 2%, 1%, 0.5%, 0.2%, 0.1%, etc. of the number itself. If there is a description of "first" or "second", it is only used for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.

[0056] In the description of the present application, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0057] The present application is described below in conjunction with specific embodiments.

[0058] Example 1

[0059] This embodiment provides an aluminum-plastic film coating, and the preparation process is as follows:

[0060] 1) Weigh 2.0 kg of γ-alumina (Mohs hardness 6.5, specific surface area 168 m 2 / g), 18kg of the first solvent NMP and 0.25kg of an aluminate coupling agent are added into a ball mill, and the ball mill cooling circulation device is turned on. During the ball milling process, the temperature is controlled below 50°C, the ball mill parameter is 30Hz, the ball milling medium is alumina, the stirring time is 1h, and the stirring is stopped to obtain a primary slurry.

[0061] 2) 0.1 g of the modifier isobutylene-maleic anhydride copolymer (ISOBAM-104) powder was evenly mixed with 0.1 L of the second solvent dimethyl carbonate to obtain a modified solution.

[0062] 3) Add 0.2 kg PVDF and the above-mentioned modified liquid to the above-mentioned primary slurry, continue stirring for 2 hours, and the ball mill parameter is 50 Hz; obtain the aluminum-plastic film coating.

[0063] This embodiment also relates to an aluminum-plastic film, Figure 1The aluminum-plastic film 100 includes a punching area 110, a side sealing area 120, a top sealing area 130, a second sealing area 140, an air pocket area 150, and a sealing area 160. In addition, the aluminum-plastic film is sequentially provided with a cast polypropylene (CPP) layer, an aluminum foil layer, and a nylon layer, and the thickness of the aluminum foil layer is 40 μm.

[0064] This embodiment also relates to a coating method of the aluminum-plastic film coating, which is specifically as follows:

[0065] Combination Figure 1 , the aluminum-plastic film coating is applied to the pit area 110 of the aluminum-plastic film CPP layer by gravure intermittent coating, and the same coating is performed on the pit back area opposite to the fold line. After hot air drying at 120°C, a first functional coating 210 and a second functional coating 220 are formed on the CPP layer to obtain an aluminum-plastic film with a functional coating, and the thickness of the functional coating is 4μm.

[0066] In addition, the first functional coating 210 covers the stamping area 110, but at the same time leaves enough space between the side sealing area 120, the top sealing area 130, the second sealing area 140 and other heat sealing areas. Specifically, the distances d1, d2, and d3 from the edge of the first functional coating 210 to the inner side of the above-mentioned heat sealing areas are all controlled to be 5 mm.

[0067] Subsequently, the aluminum-plastic film with functional coating was subjected to a punching test, with the punching depths being 5mm, 6mm, 7mm, 8mm, and 9mm respectively.

[0068] Example 2

[0069] This embodiment provides an aluminum-plastic film coating and an aluminum-plastic film with a functional coating. The difference from the embodiment 1 is that the active adsorption material is pseudo-boehmite (Mohs hardness 3.5, specific surface area 294m 2 / g).

[0070] Example 3

[0071] This embodiment provides an aluminum-plastic film coating and an aluminum-plastic film with a functional coating. Referring to Example 2, the pit depth is set to 9 mm, and the thickness of the functional coating is 2 μm, 3 μm, 4 μm, 9 μm, and 10 μm, respectively.

[0072] Example 4

[0073] This embodiment provides an aluminum-plastic film coating and an aluminum-plastic film with a functional coating. Referring to Example 1, the pit depth is set to 9 mm, and the thickness of the functional coating is 6 μm, 7 μm, and 8 μm, respectively.

[0074] Comparative Example 1

[0075] This comparative example provides an aluminum-plastic film, which is different from Example 1 in that the functional coating of Example 1 is omitted, and the pit depths are 5 mm, 6 mm, 7 mm, 8 mm, and 9 mm respectively.

[0076] Comparative Example 2

[0077] This comparative example provides an aluminum-plastic film coating and an aluminum-plastic film with a functional coating, which is different from Example 1 in that the modifier ISOBAM-104 is not added to the aluminum-plastic film coating.

[0078] Comparative Example 3

[0079] The difference from implementation 1 is that γ-alumina (Mohs hardness 6.5, specific surface area 168m 2 / g) was replaced with KS6 graphite (Mohs hardness 1, specific surface area 17m 2 / g).

[0080] Test Preparation

[0081] The aluminum-plastic films in Example 1 and Example 2 and Comparative Examples 1, 2 and 3 are used in a 1.5Ah soft-pack laminated lithium-ion battery, the depth of the aluminum-plastic film punching is 1.1 times the thickness of the bare battery cell, and a single punching method is adopted; the lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, the positive electrode active material adopts NCM ternary material, and the negative electrode active material adopts graphite; after coating, rolling, die-cutting, lamination, welding, heat sealing, baking, liquid injection, formation, capacity division and other processes, a finished battery cell is obtained.

[0082] Performance Testing

[0083] Test 1

[0084] After the punching of Example 1 and Example 2 and Comparative Example 1, the residual rate of the R-corner Al layer was tested, and the residual rate = the thickness of the R-corner aluminum layer after punching / the original thickness of the aluminum layer; the industry generally requires that the residual rate of the R-corner aluminum foil is >50%, and the results are as follows:

[0085] Table 1. R-corner aluminum foil residual rate of the examples and comparative examples

[0086]

[0087] It can be seen from the results in the table that after the improvement of the functional coating of the embodiment, at different punching depths, the residual rate of the Al layer at the R corner of the aluminum-plastic film after punching is significantly improved, and its functional coating has impact resistance at high punching depth.

[0088] Test 2

[0089] After the finished battery cell was placed at 100% SOC and 85°C for 10 days, the liquid drop volume V1 was measured by the drainage method, and the gas production = V1. The results are shown in the following table:

[0090] Table 2. Gas production of examples and comparative examples

[0091] Serial number Gas production ml Comparative Example 1 2.8 Comparative Example 2 1.6 Comparative Example 3 2.7 Example 1 0.2 Example 2 0.3

[0092] It can be seen from the results in the table that after the improvement of the functional coating of the embodiment, the gas production of the finished battery cell has decreased significantly, and the aluminum-plastic film with the functional coating has the function of adsorbing the gas inside the battery cell. Although the gas production of the finished battery cell of the functional coating of Comparative Example 2 without the addition of the modifier has decreased, the decrease of the coating without the addition of the modifier is larger. This is because the moisture content of the coating layer is large, the gas production will also increase accordingly, and the adsorption effect will be reduced. The functional coating of Comparative Example 3 is obtained by using a porous material with a lower Mohs hardness and a smaller specific surface area. The gas production of the finished battery cell is comparable to that of Comparative Example 1 without the functional coating.

[0093] Test 3

[0094] The aluminum-plastic films in Example 1 and Comparative Example 2 were subjected to the baking process according to the test preparation 1), and the moisture content of the coating area was tested using a Karl Fischer moisture tester. The results are shown in the following table:

[0095] Table 3. Comparison of different moisture contents

[0096] Serial number Moisture (ppm) Example 1 200 Comparative Example 2 600

[0097] It can be seen from the results in the table that when the modifier is omitted, the moisture content in the coating area of ​​the aluminum-plastic film functional coating increases significantly. Therefore, adding a modifier can effectively improve the capillary water absorption phenomenon of the active adsorption material.

[0098] Test 4

[0099] After coating the functional coating on Example 3 and Example 4, the residual rate of the R-corner aluminum foil layer was tested with Comparative Example 1 and Comparative Example 3. The residual rate = the thickness of the R-corner aluminum foil layer after punching / the original thickness of the aluminum foil layer. The industry generally requires that the residual rate of the R-corner aluminum foil is greater than 50%. The results are as follows:

[0100] Table 4. Effect of different coating thickness on R corner residual rate

[0101]

[0102] From the results in the table, we can see that when the Mohs hardness and thickness of the selected material do not reach a certain level, the R angle residual rate is improved, but still does not meet the industry standard requirements. When the thickness is too large, the R angle residual rate meets the industry standard, but the residual rate does not change much. The material and coating thickness of the functional layer can be selected according to different requirements, referring to the following formula:

[0103] T / 1000≤M×D≤A;

[0104] Where, T is the depth of the scouring pit; T<15mm;

[0105] M is the Mohs hardness of the active adsorption material;

[0106] D is the thickness of the functional coating; 2μm≤D≤10μm;

[0107] A is the thickness of the aluminum foil layer of the aluminum-plastic film.

[0108] The present application is described in detail above in conjunction with the embodiments, but the present application is not limited to the above embodiments, and various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present application. In addition, the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.

Claims

1. Aluminum-plastic film coating, characterized in that: It includes active adsorption material, modifier, binder, coupling agent and oily solvent, wherein the active adsorption material has a specific surface area of ​​≥150m 2 / g and a porous material with a Mohs hardness of ≥3, wherein the modifier comprises an isobutylene-maleic anhydride copolymer.

2. The aluminum-plastic film coating according to claim 1, characterized in that: The mass ratio of the modifier to the active adsorption material is 0.00005-0.0002:1; and / or the mass ratio of the binder to the active adsorption material is 1-3:10; and / or the mass ratio of the coupling agent to the active adsorption material is 1-3:

10.

3. The aluminum-plastic film coating according to claim 1, characterized in that: The active adsorption material includes at least one of γ-alumina, titanium oxide, boehmite, and pseudo-boehmite; and / or the binder includes at least one of polyvinylidene fluoride, styrene-acrylic acid copolymer, and polyvinyl acetate; and / or the coupling agent includes at least one of an aluminate coupling agent, a phthalate coupling agent, a silane coupling agent, a phosphate coupling agent, and a borate coupling agent.

4. The aluminum-plastic film coating according to claim 1, characterized in that: The oily solvent includes a first solvent and a second solvent; Wherein, the first solvent comprises at least one of N-methylpyrrolidone, dimethylformamide, carbon tetrachloride, toluene dichloroethane, acetone, and isopropanol; The second solvent includes at least one of dimethyl carbonate and N,N-dimethylformamide.

5. The aluminum-plastic film coating according to claim 4, characterized in that: The mass ratio of the first solvent to the active adsorption material is 100:10-15; and / or the ratio of the modifier to the second solvent is 1g:0.5-1.5L.

6. Aluminum-plastic film, characterized in that: The aluminum-plastic film comprises a first insulating polymer layer, an aluminum foil layer and a second insulating polymer layer which are arranged in sequence. A functional coating is also provided on the side of the first insulating polymer layer away from the aluminum foil layer. The functional coating is made of the aluminum-plastic film coating according to any one of claims 1 to 7.

7. The aluminum-plastic film according to claim 6, characterized in that: The aluminum-plastic film comprises a crater area, and the functional coating covers the crater area.

8. The aluminum-plastic film according to claim 7, characterized in that: The aluminum-plastic film satisfies T / 1000≤M×D≤A; Wherein, T is the depth of the scouring pit and is less than 15 mm; M is the Mohs hardness of the active adsorption material; D is the thickness of the functional coating, and D is 2 to 10 μm; A is the thickness of the aluminum foil layer.

9. A lithium-ion battery, characterized in that The invention comprises the aluminum-plastic film according to any one of claims 6 to 8.

10. Electrical equipment, characterized in that: Includes the lithium ion battery as claimed in claim 9.

Citation Information

Patent Citations

  • Metal composite film capable of adsorbing gas, preparation method of metal composite film and bagged battery

    CN113889711A

  • Isolating membrane, preparation method thereof, and related secondary battery and electric device

    CN116964849A

  • Metal composite film capable of adsorbing gas and preparation method therefor, and pouch battery

    WO2023035762A1